2014
DOI: 10.1016/j.celrep.2014.08.043
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Presentation of Self-Lipids by Autoimmune B Cells Depletes Peripheral iNKT Cells

Abstract: Invariant natural killer T (iNKT) cells provide cognate help via CD1d to lipid antigen-presenting B cells for antibody production, but whether B cells reciprocally regulate iNKT cells remains largely unexplored. Here, we found peripheral, but not thymic, iNKT cells to be numerically reduced in autoimmune mice lacking Fas specifically in B cells. The residual iNKT cells were antigenically overstimulated, had altered cytokine production, and manifested enhanced proliferation and apoptosis. B cell-specific ablati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…For example, the loss of CD1d expression on B cells, following Epstein–Barr virus infection, results in severe attenuation of iNKT cell functions 49 . Data from our laboratory and confirmed by other groups 1 , 50 suggested that aberrant CD1d expression by B cells is associated with iNKT cell functional defect observed in SLE patients. These findings suggest that CD1d-mediated B-iNKT cell cross talk may be important in iNKT cell homeostasis and for regulation of suppression.…”
Section: Discussionsupporting
confidence: 83%
“…For example, the loss of CD1d expression on B cells, following Epstein–Barr virus infection, results in severe attenuation of iNKT cell functions 49 . Data from our laboratory and confirmed by other groups 1 , 50 suggested that aberrant CD1d expression by B cells is associated with iNKT cell functional defect observed in SLE patients. These findings suggest that CD1d-mediated B-iNKT cell cross talk may be important in iNKT cell homeostasis and for regulation of suppression.…”
Section: Discussionsupporting
confidence: 83%
“…Mouse liver tissue was harvested, flash frozen in liquid nitrogen and stored at −80 °C prior to extraction. Subsequently, 50 mg of tissue was homogenized at 4 °C and metabolites extracted as described previously 44 using a mixture of cold methanol, tricine and chloroform. The lipid fraction (chloroform layer) was then collected and stored at −80 °C.…”
Section: Methodsmentioning
confidence: 99%
“…NKT cells contribute to autoimmune diseases either through defective immunoregulation or inappropriate activation . A recent study has also shown that autoimmune B cells, via altered presentation of self‐lipids by CD1d, cause overt activation of NKT cells, leading to NKT cell death . Because NKT cell/B‐cell interactions are important in driving normal humoral responses as well as autoimmunity, it would be interesting to study the role of the JAK/STAT pathway in regulating CD1d‐mediated antigen presentation under those conditions.…”
Section: Discussionmentioning
confidence: 99%